Determinants of household savings in South Africa (2012)
M.Comm. === Household savings is an important instrument for any economy and is also a crucial determinant of welfare in developing countries. This study investigates the determinants of household savings in South Africa and the factors that influences the current declines experienced in household savings. Household variables such as household income, expenditure, debt, as well as interest rates were analysed using trends to reveal their specific effect to the overall household savings. The Permanent Income Hypothesis emphasises the notion that people save because they expect a decline in their future income, meaning that savings should be a good predictor of a decline in income. Cointegration analysis on South African Reserve Bank data from 1990Q1 to 2009Q3 was conducted and results revealed that with all variables included, household income is the main determinant of household savings in South Africa. Impulse response functions, variance decomposition functions, as well as the granger-causality test were performed and results showed that household income remains the main determinant of household savings.